MiRNA-221 from tissue may predict the prognosis of patients with osteosarcoma. Issue 29 (July 2018) - Gong, Ningji; Gong, Mingzhi
Abstract : Abstract: This study was aimed to investigate the relationship between miR-221 expression and prognosis in patients with osteosarcoma. miR-221 expression in 69 osteosarcoma specimens and corresponding noncancer tissues were characterized by quantitative reverse transcription polymerase chain reaction. The associations of miR-221 expression with clinicopathologic factors and prognosis in patients with osteosarcoma were statistically analyzed. miR-221 expression in patients with osteosarcoma was significantly higher than in the corresponding noncancer tissues ( P < .01). miR-221 overexpression was significantly associated with tumor stage, metastatic status, and response to chemotherapy pretreatment. Cox regression analysis revealed that miR-221expression, metastasis, and response to chemotherapy were independent prognostic indicators for osteosarcoma. miR-221 upregulation may predict clinical outcomes in patients with osteosarcoma.